Dal Trattato di anatomia di Leonardo alle unità fraseologiche - Messina Fajardo, Luisa A. (Dialogoi. Rivista di studi comparatistici, 2020)
There are several central points of this study based on the analysis of phraseological somatisms. First of all, the terminological dispersion present in phraseological studies centered on the human body is highlighted (phraseological somatisms, somatic expressions, idiomatic somatisms, corporal expressions, ...). The intention is to standardize the terminology that could otherwise create confusion, as already happens with the phraseological dispersion present to define the object of study of the phraseology (idiomatic expression, superior lexical unit, complex lexeme, polirematic unit, idiom, fixed expression, proverbs, sayings, ...). Second, phraseological somatisms are studied starting from the characteristics and classifications proposed by Corpas Pastor (1996) and Alberto Zuluaga (1980). The relative stability and the unitary, and almost always idiomatic meaning of the UF are highlighted. Third, we focus on the topic of the classification of UF, one of the most controversial points of the discipline and, also, one of the most studied (Wotjak, 2000; Zuluaga, 1980, Corpas, 1996; Penadés, 2018; García-Page, 2008). From a methodological point of view, our corpus is built starting from Il Trattato di Anatomia Emozionale by Virginia Caldarella and Andrea Pennisi (2018), which are inspired by Leonardo Da Vinci’s Treatise on Anatomy. Finally, with the (functional) analysis that we offer, we demonstrate what Inmaculada Penadés (2018: p. 714) affirms regarding the double possibility of classification that many UF (loc. v. / loc. s.: (Avere) ali ai piedi; loc. adj. / loc. v (Avere) cuore ardente, …).